ANALISIS STRATEGI DAN TANTANGAN RESELLER DALAM BISNIS ONLINE FASHION MUSLIM: PENDEKATAN KUALITATIF PADA RESELLER GAMIS DAN HIJAB DI PEMALANG - Diya Ayu Luspita Wulansuci (PT. Intelek Cendikiawan Nusantara, 2025)
The development of digital technology and social media has opened up great opportunities for people to do business online. One form of business that is growing rapidly is the reseller system, whereby individuals purchase products from suppliers to resell them online. This study aims to analyze the strategies, opportunities, and challenges faced by resellers of Muslim fashion products, particularly gamis and hijabs, in Pemalang Regency. The research method used is qualitative with an empirical approach, through observation and direct interviews with business actors. The results show that the success of a reseller business is greatly influenced by personal motivation, digital marketing creativity, consistency in promotion, and the ability to build customer trust. Social media such as WhatsApp, Facebook, and TikTok play an important role in expanding market reach and strengthening personal branding. However, limited capital, dependence on suppliers, and technical obstacles such as delivery delays are major challenges that must be overcome. In conclusion, the Muslim fashion reseller business has promising economic potential if managed with innovative digital marketing strategies that are adaptive to technological developments.